Staff resilience and innovation essential to New York City diabetes prevention programs going virtual during COVID-19 pandemic lockdowns - Eleanor J. Smith; Leora J. Apfelbaum; Ming-Chin Yeh; Margrethe F Horlyck-Romanovsky (BMC, 2023)
Abstract Background COVID-19 lockdowns in March 2020 forced National Diabetes Prevention Programs (DPPs) to pause, cancel or reformulate. This qualitative study sought to (a) document if/how New York City(NYC) DPPs adapted and served participants during lockdowns, and (b) identify successes and challenges to operating programs during the lockdowns and restrictions on social gathering. Methods Researchers contacted 47 CDC-registered DPPs in NYC. Eleven DPP directors, lifestyle coaches, and coordinators involved in program implementation completed 1-hour semi-structured virtual interviews and received a $50 gift card. Interviews were recorded, transcribed, and analyzed using Grounded Theory (Dedoose, Version 9). Results Interviewees represented 7 organization types: public hospitals, weight loss programs, healthcare centers, community-based organizations, health insurance companies, faith-based DPPs, and federally qualified health centers. DPPs served participants in 4 of 5 NYC boroughs. Six organizations provided DPP services during lockdowns by going virtual. Successes and challenges related to staffing, resource allocation, virtual data tracking, and participant engagement. Most programs were successful due to resilient, dedicated, and extraordinarily innovative staff. Conclusion The pandemic highlighted opportunities for successful virtual DPPs in urban settings, and the need for more robust funding, staff support, and technical assistance for sustainability and scalability of the DPP.